Determination of suspected non halal food products by using porcine mitochondrial 12s rDNA and porcine leptin gene / Khairunnisa Hassan - Hassan, Khairunnisa (2016)
In the current era of market globalization, people in the world could not evade from imported food products. The demand for imported food products such as chocolates, biscuits and sweets are projected to escalate steadily over the next decade as a result of increasing consumption. Unfortunately, most of the imported food products do not have Halal Logo or with doubted Halal Logo. The demand for Halal food and other Islamic consumer goods is increasing. This study will be beneficial to provide new information of Halal products and easier for Muslim to choose the permissible products according to Syariah Law. The main objective of this study was to determine of suspected Non Halal processed food products by using porcine mitochondrial 12S rDNA and porcine leptin gene. A total of 66 samples of suspected Non Halal food products were screened for porcine mitochondrial 12S rDNA gene and porcine leptin gene primer pairs from the genomic DNA. The PCR products were separated on 2% agarose gel and visualized under UV light. Thirty seven samples were positive with mitochondrial 12S rDNA gene whilst 59 samples were positive with leptin gene. From these, 33 were positive with both primers. These results indicate that the samples of processed food products contained porcine derivatives. From the detection of the DNA products by using the two set of primers, leptin gene was concluded to be more specific than the mitochondrial 12S rDNA gene. Some of the PCR products of processed food products of mitochondrial 12S rDNA gene and leptin gene were sent to Genomic Bioscience & Technology Company for DNA sequencing. Then, the sequences of the DNA were used for sequence alignment in order to get a probe specific to Halal food. Two probes were obtained, one with 24 mers and 13 mers, respectively. Mitochondrial 12S rDNA gene was chosen to make a probe because it has more quality DNA for a probe compared to leptin gene. In addition, findings from this research also provide new information in the detection of pork in foods products for Halal authentication.